2016
DOI: 10.1038/srep31690
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of the NR4A3 tumor suppressor, by aberrant JAK/STAT signaling, predicts prognosis in gastric cancer

Abstract: While aberrant JAK/STAT signaling is crucial to the development of gastric cancer (GC), its effects on epigenetic alterations of its transcriptional targets remains unclear. In this study, by expression microarrays coupled with bioinformatic analyses, we identified a putative STAT3 target gene, NR4A3 that was downregulated in MKN28 GC daughter cells overexpressing a constitutively activated STAT3 mutant (S16), as compared to an empty vector control (C9). Bisulphite pyrosequencing and demethylation treatment sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 50 publications
3
38
1
Order By: Relevance
“…Among these genes, we noted NR4A3, which was up‐regulated after LINC00467 knockdown and inversely associated with LINC00467 in HCC tissues. NR4A3 is a member of nuclear receptors superfamily and frequently reported to act as a tumour suppressor in gastric, breast and lung cancer . Therefore, we further investigated whether LINC00467 regulates NR4A3 and whether the modulation of NR4A3 mediates the oncogenic roles of LINC00467 in HCC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these genes, we noted NR4A3, which was up‐regulated after LINC00467 knockdown and inversely associated with LINC00467 in HCC tissues. NR4A3 is a member of nuclear receptors superfamily and frequently reported to act as a tumour suppressor in gastric, breast and lung cancer . Therefore, we further investigated whether LINC00467 regulates NR4A3 and whether the modulation of NR4A3 mediates the oncogenic roles of LINC00467 in HCC.…”
Section: Resultsmentioning
confidence: 99%
“…NR4A3 (orphan nuclear receptor 4A3) belongs to the nuclear receptor superfamily. NR4A3 has been shown to regulate cell proliferation, apoptosis and migration and have generally tumour‐suppressive roles in breast cancer, lung cancer, gastric cancer and leukaemia . Therefore, we hypothesized that the tumour suppressor NR4A3 may mediate the oncogenic roles of LINC00467 in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether STAT3 affects the expression of GATA6 directly, we examined the binding status of STAT3 in AGS cells showing constitutive activation of STAT3 [ 15 , 16 ]. The binding of STAT3 can be observed at the putative STAT3 binding site upstream of the GATA6 promoter ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…In response to interleukin-6 signal, STAT3 could be activated and is involved in various types of pathological conditions. STAT3 plays important roles in various types of cancer 3335. Yu et al found that activated STAT3 was correlated with prognosis of NSCLC 36.…”
Section: Discussionmentioning
confidence: 99%